Terahertz Non-Destructive Testing and Imaging of High-Voltage Cables - Zhenwei, Zhang; Jing, Xu; Rui, Jia; Yinghong, Wu; Hao, Guan; Siyi, Han; Cunlin, Zhang; Yuejin, Zhao (Frontiers in Physics, 2022)
The evaluation of the internal defects in high-voltage cross-linked polyethylene cables is highly crucial for the security and reliability of power transmission. Here, a terahertz (THz) frequency-modulated-continuous-wave non-destructive testing (NDT) imaging system is used to demonstrate the non-contact detection of a high-voltage cable (35 KV). Combined with linear scanning and axial rotation, the three-dimensional (3D) data of the columnar target is acquired, and a 3D perspective image is reconstructed. The correspondence between the target in the real space and image space is determined to accurately show the internal spiral structure and strand number of metal wires. The results indicate that prefabricated air and water holes in the polyethylene insulation layer can be displayed. Furthermore, feature defect signals are automatically classified and recognised by combining the principal component analysis dimension reduction method and the support vector machine classification method, which can predict abnormal defects more efficiently in mass data. These results provide technical guidance for the non-contact NDT and visual evaluation of the internal state of detected cable targets.